Design and Development of Emergency Mobile Application Using Design Thinking and Agile Scrum: A Case Study of Batam City - Li Cen; Martius Lim; Ricky Roy Nardson; Herman (Program Studi Ilmu Komputer, Universitas Pakuan, 2026)
Emergency response in Batam City, an area with high urban mobility and dynamics, is often hamperedby slow reporting mechanisms. Residents must contact different numbers for each service in differentareas, such as the fire department, ambulance, or police, causing confusion and wasting valuable time,especially in panic situations. The absence of an integrated system specifically creates significantinefficiencies in emergency service response. This study aims to design and develop an integrated mobileapplication that serves as a tool to accelerate the reporting and handling of emergency conditions andpublic utility services in Batam City. The methodology used combines the Design Thinking approach,which ensures that solutions are designed based on the real needs and experiences of users, with the AgileScrum method, which allows for a flexible and iterative development process. This research successfullyproduced a functional application that was then comprehensively tested. Functionality testing using theUsability Testing Method showed that all core features worked well, were valid, and performed asexpected. To measure usability, a System Usability Scale (SUS) test was conducted, resulting in anexceptional score of 88.82. This score places the application in the “Excellent” category, with an“Acceptable” user acceptance rating, indicating a highly intuitive and easy-to-use interface. The mainconclusion is that the developed application has proven to be highly viable, functional, and well-receivedby users. This application shows significant potential as an effective tool for improving the speed andefficiency of emergency service responses, and could serve as a model technological solution for publicservice integration in the City of Batam.